2022
DOI: 10.1038/s41586-022-04744-8
|View full text |Cite
|
Sign up to set email alerts
|

Ordered and tunable Majorana-zero-mode lattice in naturally strained LiFeAs

Abstract: Majorana zero modes (MZMs) obey non-Abelian statistics and are considered building blocks for constructing topological qubits 1,2 . Iron-based superconductors with topological band structures have emerged as promising hosting materials, since isolated candidate MZMs in the quantum limit have been observed inside the topological vortex cores 3-9 . However, these materials suffer from issues related to alloying-induced disorder, uncontrolled vortex lattices 10-13 and a low yield of topological vortices 5-8 . Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 46 publications
1
33
0
4
Order By: Relevance
“…We have attempted to outline three of the tuning knobs in acquiring one or both of the essential ingredients of TSC, including strain, gating, and ferroelectricity. In particular, strain has been demonstrated very recently as an effective means to regulate the spatial distribution and mutual interaction of a MZM lattice [64]. Furthermore, we optimistically expect that the reversible and nonvolatile ferroelectric tunability will play a major role in gaining precise control and manipulation of MZMs.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We have attempted to outline three of the tuning knobs in acquiring one or both of the essential ingredients of TSC, including strain, gating, and ferroelectricity. In particular, strain has been demonstrated very recently as an effective means to regulate the spatial distribution and mutual interaction of a MZM lattice [64]. Furthermore, we optimistically expect that the reversible and nonvolatile ferroelectric tunability will play a major role in gaining precise control and manipulation of MZMs.…”
Section: Discussionmentioning
confidence: 97%
“…Beyond FeSe-based superconductors, impurity-assisted vortex states in LiFeAs have also been shown to exhibit MZMs [294], attesting the nontrivial nature of the superconducting systems. Furthermore, as a compelling example for the strain-based tunability, a very recent study reported that the surface strain can alter the charge density waves (CDWs) appearing on the surfaces of the LiFeAs, and such CDWs can in turn regulate the special distribution of the vertex lattice that harbors the MZMs [64]. More coverages on this line of advances can be found in a separate review within this volume [295].…”
Section: A Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the Majorana-zero-mode lattice has been realized in a tunable way 53 , which provides a natural platform to implement interacting Majorana fermion model composed of local interactions only. A theoretically interacting question is the doping effect, that is doping on γ or χ Majorana fermions to study the effect on AFM order or quantum spin liquid, which may provide clues to high-T c cuprates.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Zero-bias conductance peak (ZBCP) has also been reported as a Majorana feature in spectroscopic measurements of vortex states via the standard scanning tunneling microscopy (STM) technique [23][24][25][26][27][28][30][31][32][33][34][35][36][37]. More inspiringly, a recent progress [53] shows that topological vortexes can form into an ordered lattice through the introduction of a biaxial charge density wave. This technical advance can potentially reduce the difficulty of Majorana manipulation: the next stage in the realization of topological quantum computation.…”
Section: Introductionmentioning
confidence: 99%